The role of epigenetics in childhood autoimmune diseases with hematological manifestations - Athanasios Gkoutsias; Alexandros Makis (Wiley, 2022)
ABSTRACT Autoimmune diseases with hematological manifestations are often characterized by chronicity and relapses despite treatment, and the underlying pathogenetic mechanisms remain unknown. Epigenetic alterations play a vital role in the deregulation of immune tolerance and the development of autoimmune diseases. In recent years, study of epigenetic mechanisms in both adult and childhood autoimmune disorders has been seeking to explain the pathophysiology of these heterogeneous diseases and to elucidate the interaction between genetic and environmental factors. Various mechanisms, including DNA methylation, histone modifications (chromatin remodeling), and noncoding RNAs (ncRNAs), have been studied extensively in the context of autoimmune diseases. This paper summarizes the epigenetic patterns in some of the most common childhood autoimmune disorders with hematological manifestations, based on epigenetic studies in children with primary immune thrombocytopenia (ITP), systemic lupus erythematosus (SLE), and juvenile idiopathic arthritis (JIA). Research findings indicate that methylation changes in genes expressed on T cells, modifications at a variety of histone sites, and alterations in the expression of several ncRNAs are involved in the pathogenesis of these diseases. These mechanisms not only determine the development of these diseases but also affect the severity of the clinical presentation and biochemical markers. Further studies will provide new tools for the prevention and diagnosis of childhood autoimmune disorders, and possible novel treatment options.